1976
DOI: 10.1103/physrevlett.36.382
|View full text |Cite
|
Sign up to set email alerts
|

Josephson Oscillation of a Moving Vortex Lattice

Abstract: Experimental evidence is presented for a supercurrent oscillation arising from vortex motion in the flux-flow regime of superconducting films with periodically modulated thickness. An essential condition for detecting the rf electric field associated with the oscillation is matching of the vortex lattice to the periodic pinning structure represented by the thickness modulation.This Letter reports the observation of radiofrequency (rf) electric fields in the flux-flow regime of type-II superconducting films wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 13 publications
0
33
0
2
Order By: Relevance
“…Shapiro step phenomena also arise in dc and ac driven charge density waves [7][8][9] , spin density waves 10 , and Frenkel-Kontorova models consisting of commensurate or incommensurate arrangements of particles moving over ordered or disordered substrates [11][12][13] . In the case of vortex motion in type-II superconductors, Martinoli et al reported the first observation of Shapiro steps for dc and ac driven vortices interacting with a periodic one-dimensional (1D) substrate created by periodic thickness modulations of the sample 14,15 , while similar effects were observed for vortices driven over 1D 16,17 or two-dimensional (2D) 18,19 periodic substrates. More recently, Shapiro steps have been found for ac and dc driven colloidal particles moving over a quasi-1D periodic substrate 20 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Shapiro step phenomena also arise in dc and ac driven charge density waves [7][8][9] , spin density waves 10 , and Frenkel-Kontorova models consisting of commensurate or incommensurate arrangements of particles moving over ordered or disordered substrates [11][12][13] . In the case of vortex motion in type-II superconductors, Martinoli et al reported the first observation of Shapiro steps for dc and ac driven vortices interacting with a periodic one-dimensional (1D) substrate created by periodic thickness modulations of the sample 14,15 , while similar effects were observed for vortices driven over 1D 16,17 or two-dimensional (2D) 18,19 periodic substrates. More recently, Shapiro steps have been found for ac and dc driven colloidal particles moving over a quasi-1D periodic substrate 20 .…”
Section: Introductionmentioning
confidence: 98%
“…In this work we examine Shapiro steps for skyrmions moving over a quasi-1D periodic washboard substrate similar to the geometry considered by Martinoli et al for vortices moving over substrates with a periodic thickness modulation [14][15][16] . We consider the motion of single skyrmions and collectively interacting skyrmions over a periodic substrate, as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This was based on the experimental fact that the washboard noise had not been observed in the vortices of superconductors before, except in a system with artificially introduced strong periodic pinning centers [16] and in the thermally-excited motion of a limited number of vortices [17].…”
Section: Introductionmentioning
confidence: 99%
“…Большой цикл работ по исследованию смешанного состояния в гофрирован ных сверхпроводящих пленках выполнен Мартиноли с соавторами [68][69][70][71][72][73]. При этом использовались пленки алюминия, напыленные в атмосфере кисло рода.…”
Section: 2unclassified
“…Положения этих ступенек определялись соотношением где -целые числа. Более того, в работе [70] было зарегистрировано непосредственно электро магнитное излучение при движении вихревой решетки в гофрированной плен ке. Оказалось, что реализовать когерентное движение вихрей необычайно сложно.…”
Section: 2unclassified